2004
DOI: 10.1093/molbev/msi049
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Diversifying Selection in the Phytotoxin-like scr74 Gene Family of Phytophthora infestans

Abstract: Phytophthora infestans, the organism responsible for the Irish famine, causes late blight, a re-emerging disease of potato and tomato. Little is known about the molecular evolution of P. infestans genes. To identify candidate effector genes (virulence or avirulence genes) that may have co-evolved with the host, we mined expressed sequence tag (EST) data from infection stages of P. infestans for secreted and potentially polymorphic genes. This led to the identification of scr74, a gene that encodes a predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
106
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(113 citation statements)
references
References 84 publications
(102 reference statements)
7
106
0
Order By: Relevance
“…The abundance of some domains in plant pathogens is too low to be identified as being overrepresented. For example, the PcF domain (IPR018570), which is present in a small, approximately 50-amino acid necrosis-inducing protein found in various Phytophthora species (Orsomando et al, 2001;Liu et al, 2005), was not identified in the initial overrepresentation analysis. Also in this cluster is the sugar fermentation stimulation domain (IPR005224), which is mainly found in bacteria and involved in the regulation of maltose metabolism (Kawamukai et al, 1991).…”
Section: Clustering Of Abundance Profiles Reveals Additional Potentiamentioning
confidence: 99%
“…The abundance of some domains in plant pathogens is too low to be identified as being overrepresented. For example, the PcF domain (IPR018570), which is present in a small, approximately 50-amino acid necrosis-inducing protein found in various Phytophthora species (Orsomando et al, 2001;Liu et al, 2005), was not identified in the initial overrepresentation analysis. Also in this cluster is the sugar fermentation stimulation domain (IPR005224), which is mainly found in bacteria and involved in the regulation of maltose metabolism (Kawamukai et al, 1991).…”
Section: Clustering Of Abundance Profiles Reveals Additional Potentiamentioning
confidence: 99%
“…Like Arabidopsis R genes, however, the Phyophthora infestans scr74 gene family of effectors may be subject to diversifying selection (Liu et al 2005). Limited evidence of balancing selection acting upon virulence-related genes is found in Fusarium graminearum (Ward et al 2002) and in Borrelia burgdorferi (Qiu et al 2004).…”
mentioning
confidence: 99%
“…1, top), interestingly including all six SSbridged cysteines of PcF recognized as essential for structuring its helix-loop-helix core domain. 22 Notably, only the SCR74 species possess two extra cysteines and thus one presumed additional SS bridge, not shared by other family members 20 ( Fig. 1, bottom).…”
Section: Bacterial Over-expression and Mutagenesis Strategymentioning
confidence: 99%
“…20 Overall, these hints suggest conserved protein folds and functions. To date, however, PcF remains the only characterized member within its family.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation